Investigate lipid and protein oxidation in herring (\(Sardinella gibbosa\)) by sodium acetate during preservative time - Doan, Thi Thiet; Pham, Xuan Ky; Dao , Viet Ha; Nguyen, Phuong Anh; Le Ho, Khanh Hy; Phan, Bao Vy (Vietnam Journal of Marine Science and Technology, 2023)
The study was carried out to investigate lipid and protein oxidation of herring (Sardinella gibbosa) that was treated with (2.5% w/v) sodium acetate at 4oC. After 3, 6, 9, and 12 days, lipid and protein oxidation were evaluated by indications such as pH value, peroxide (PV), thiobarbituric acid-reactive substances (TBARS), protease enzyme activity and sulfhydryl. The results showed that, pH was from 6.33 ± 0.005 to 7.42 ± 0.005 (p < 0.05); PV was 1.73 ± 0.31 to 7.13 ± 0.5 (mEq/kg) (p < 0.05), and TBA was from 53.3 ± 0.28 μmol MDA/kg to 207.4± 0.47 μmol MDA/kg (p < 0.05). Protease enzyme activity reduced from 0.323–0.175 U/mg protein (p < 0.05), and sulfhydryl was from 14.39–7.198 µmol/g protein (p < 0.05). Consequently, sodium acetate effectively prevents lipid and protein oxidation, extending herring meat’s life.